Weather Variability, Credit Scores and Access to Credit: Evidence from Colombian Coffee Farmers (2020)
This paper studies how weather variability affects credit scores and credit access in developing countries. Using rich administrative data on loans to coffee farmers from a large Colombian bank, I show that negative weather shocks lead to lower loan repayment, lower credit scores and more frequent denials of future loan applications. I present evidence that affected farmer's income and ability to repay recover more quickly from weather shocks than credit access. Therefore, the interplay of weather variability and credit scores can lead to the exclusion from credit markets of farmers who could repay a loan.